The long-active afterglow of GRB 210204A: detection of the most delayed flares in a gamma-ray burst. Issue 2 (18th April 2022) - Kumar, Harsh; Gupta, Rahul; Saraogi, Divita; Ahumada, Tomás; Andreoni, Igor; Anupama, G C; Aryan, Amar; Barway, Sudhanshu; Bhalerao, Varun; Chandra, Poonam; Coughlin, Michael W; , Dimple; et al.
ABSTRACT: We present results from extensive broadband follow-up of GRB 210204A over the period of 30 d. We detect optical flares in the afterglow at 7.6 × 10 5 s and 1.1 × 10 6 s after the burst: the most delayed flaring ever detected in a GRB afterglow. At the source redshift of 0.876, the rest-frame delay is 5.8 × 10 5 s (6.71 d). We investigate possible causes for this flaring and conclude that the most likely cause is a refreshed shock in the jet. The prompt emission of the GRB is within the range of typical long bursts: it shows three disjoint emission episodes, which all follow the typical GRB correlations. This suggests that GRB 210204A might not have any special properties that caused late-time flaring, and the lack of such detections for other afterglows might be resulting from the paucity of late-time observations. Systematic late-time follow-up of a larger sample of GRBs can shed more light on such afterglow behaviour. Further analysis of the GRB 210204A shows that the late-time bump in the light curve is highly unlikely due to underlying SNe at redshift (z) = 0.876 and is more likely due to the late-time flaring activity. The cause of this variability is not clearly quantifiable due to the lack of multiband data at late-time constraints by bad weather conditions. The flare of GRB 210204A is the latest flare detected to date.